(3OhQ dLfI GdCee GdeJMOI dbGfhf GdJLGQI GdOhdjI aj JhMjO bhGYOg (B/ s - (3HgLJ UdGM Ydj CMeOs; (3eMehO SejQ GdTQbGhj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 2009)
(3JfbSe GdQSGdI Edi GdaUd GdJegjOj hGdPj jJfGhd GdefXeGJ GdegJeI HJhMjO bGfhf GdJLGQI GdOhdjI, Ke GdHGH GdChd GdPj jHOC aj JfGhd dLfI GdGee GdeJMOI dbGfhf GdJLGQI GdOhdjI, Ke GdHGH GdKGfj Yf GdbhGYO GdehMOI GdUGOQI Yf GddLfI aj HYV GdehVhYGJ, hCNjQG GdHGH GdKGdK GdPj jJfGhd Jbjje OhQ GddLfI aj hVY hJhMjO GMcGe bGfhf GdJLGQI GdOhdjIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2009.s
(3HHdjhLQGajG(B: (3UaMGJ(B352-369.s
Keywords: (3GdefXeGJ GdegJeI HJhMjO bGfhf GdJLGQI GdOhdjIs; (3dGgGi ddHjY GdOhdj ddefbhdGJ GdeGOjI s; (3GdLeYjI GdOhdjI ddYdhe GdbGfhfjIs; (3GdLeYjI GdOhdjI ddYdhe GdbGfhfjIs; (3eTQhY GdbGfhf GdfehPLj ddJMcje GdJLGQi GdOhdjs; (3GJaGbjI GdCee GdeJMOI GdeJYdbI HGdVeGfGJ GdeSJbdI hNWGHGJ GdGYJeGO GdVGefIs; (3GdefXeGJ GdegJeI HJhMjO bGfhf GdJLGQI GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2009